If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3=t
We simplify the equation to the form, which is simple to understand
-3=t
We move all terms containing t to the left and all other terms to the right.
-1t=+3
We simplify left and right side of the equation.
-1t=+3
We divide both sides of the equation by -01 to get t.
t=-3
| 29=9x+2-6x | | 10/200=0.05 | | x/7+7=13 | | (x+3)+7=90-34x | | 3.14*25= | | 2+z=4+10 | | 3y^4-48= | | cos(x)=.3(x) | | 6(x)+3=4(x)+11 | | 7/x-(3/2x)+7/6 | | 6x+(90-x)=180 | | 20=4+3x+x | | 13(27)-13(7)= | | c^2+6c+14= | | 5/6(2x-5)=1/4(3x-7) | | -3/5=-3/2+s | | -2x-1=-3x-4 | | 12k=9k-15 | | 4-100/8v+15 | | m/4=25 | | -6(-7b+3)+4=-2b+30 | | 7/x-(3/2x)+7/6=9/x | | 7/3=-5/2+z | | b-4+8b=27 | | x/4-8=-12 | | (y+5/y^2+2y)-(6/y^2-4)=0 | | 6y+8x=7 | | 12(83)+88(93)= | | 4m+2mn+m^2=m+3m^2 | | -5/7=p/35 | | (14+7x).5+3=6.5 | | 7/z-4=8 |